A Case of Schizencephaly and Septo-Optic Dysplasia Presenting with Anterior Encephalocele - FADAKAR, Kaveh; DADKHAHFAR, Sahar; ESMAEILI, Arash; KEYHANIDOUST, Zarrintaj (Iranian Journal of Child Neurology, 2013)
How to cite this article: Fadakar K, Dadkhahfar S, Esmaeili A, Keyhanidoust Z. A Case of Schizencephaly and Septo-Optic Dysplasia Presenting with Anterior Encephalocele. Iran J Child Neurol Autumn 2012; 6(4):47-50. Abstract Schizencephaly is a rare central nervous system disorder with variable presentations. Here we report a patient with a huge bilateral schizencephaly and septo-optic dysplasia presenting with anterior encephalocele. References: Yakovlev PI, Wadsworth RC. Schizencephalies; a study of the congenital clefts in the cerebral mantle; clefts with hydrocephalus and lips separated. J Neuropathol Exp Neurol. 1946 Jul;5(3):169-206. Yakovlev PI, Wadsworth RC. Schizencephalies; a study of the congenital clefts in the cerebral mantle; clefts with fused lips. J Neuropathol Exp Neurol. 1946 Apr;5:116-30. Brunelli S, Faiella A, Capra V, Nigro V, Simeone A,Cama A et al. Germline mutations in the homeobox gene EMX2 in patients with severe schizencephaly. Nat Genet. 1996 Jan;12(1):94-6. Montenegro MA, Guerreiro MM, Lopes-Cendes I,Guerreiro CA, Cendes F. Interrelationship of genetics and prenatal injury in the genesis of malformations of cortical development. Arch Neurol. 2002 Jul;59(7):1147-53. Granata T, Freri E, Caccia C, Setola V, Taroni F,Battaglia G. Schizencephaly: clinical spectrum, epilepsy, and pathogenesis. J Child Neurol. 2005 Apr;20(4):313-8. Lee HK, Kim JS, Hwang YM, Lee MJ, Choi CG, Suh DC et al. Location of the primary motor cortex in schizencephaly. AJNR Am J Neuroradiol. 1999 Jan;20(1):163-6. De Morsier G. [Studies on malformation of cranio-encephalic sutures. III. Agenesis of the septum lucidum with malformation of the optic tract]. Schweiz Arch Neurol Psychiatr. 1956;77(1):267-92. Hoyt WF, Kaplan SL, Grumbach MM, Glaser JS. Septo-optic dysplasia and pituitary dwarfism. Lancet. 1970 Apr;1(7652):893-4. Webb EA, Dattani MT. Septo-optic dysplasia. Eur J Hum Genet. 2010 Apr;18(4):393-7. Ellenberger C Jr, Runyan TE. Holoprosencephaly with hypoplasia of the optic nerves, dwarfism, and agenesis of the septum pellucidum. Am J Ophthalmol. 1970 Dec;70(6):960-7.